HVDC grid for offshore wind exploitation - E. Ciapessoni (2015)
Offshore wind has been envisaged as making a critical contribution in Europe in satisfying the electricity demand in a low-carbon generation scenario. In fact, offshore environment provides a windier and steadier source compared to onshore wind energy. Installation, operation and maintenance of offshore facilities, whether associated with the generation, collection or transmission of the electrical energy, is extremely expensive and so the correct technologies must be deployed to provide the maximum cost-benefit. For quite long distances offshore, High-Voltage Direct Current (HVDC) transmission is preferred for economic and technical reasons; hence, this technology provides the platform that can be used to enable massive integration of offshore wind farms into AC onshore networks with minimum losses and increased flexibility over power control. In case of many, large offshore wind farms, conventional point-to-point connections to-shore appear inadequate for operational, market and reliability reasons. Multi-Terminal HVDC (MTDC) grids are thus foreseen to increase flexibility and to reduce the power not supplied to onshore grids in case of DC disturbances. Voltage Source Converter (VSC) technology is the most promising converter solution for the development of offshore DC connections. Though less mature than Line Commutated Converter (LCC) technology, VSC offers significant advantages for offshore grid applications, moreover it is rapidly evolving.